أبعاد التنمية المستدامة في الجزائر وفكرة ربطها بالتجارة الدولية - بوحسون, عبد الرحمن (University of Eloued جامعة الوادي, 2019)
: لازال التاريخ البيئي للإنسان يشهد على أنه كلما ارتفعت أعداد الناس ، تعاظمت معه معدلات استهلاكهم لسلع و خدمات ، وحدوث طفرة في كمية النفايات التي تخرج عن نشاطاتهم إلى حيز البيئة ، مما تولد عنه حدوث اختلال في العلاقة المتوازنة بين الإنسان وبيئته ، وتوجس الفرد والمجتمع خوفا من خطر ذاك على مستقبلهم ، وتبلورت على اثر ذلك فكرة التنمية المستدامة . تقع التنمية المستديمة عند نقطة الالتقاء بين البيئة والاقتصاد والمجتمع،ولذلك تعمل معظم حكومات الدول على جعل سكان العالم أكثر وعيا وإدراكا و اهتماما بالبيئة ، حتى يتملكوا المعرفة والمهارة و الالتزام بالعمل كأفراد ، أو كمجموعات ، من أجل إيجاد الحلول للمشاكل البيئية والحيلولة دون نشوء مشاكل جديدة مستقبلا. جاءت هذه الدراسة لتتناول موضوع التنمية المستدامة (المفهوم ، وتحديد أبعادها.وما هي أهم التحديات التي تعترض سبل تحقيقها على أرض الواقع، ،وتوصلت في الختام إلى أهم النتائج والحلول المتوقعة للحد من الظاهرة حاضرا ومستقبلا.. تكمن أهمية هذه الدراسة في أنها تسمح بتشخيص التنمية المستدامة ومعرفة مختلف التحديات التي تواجهها الجزائر في هذا المجال. Abstract: The environmental history of a person continues to testify that the higher the number of people, the greater their consumption of goods and services, and a surge in the amount of waste that goes out of their activities into the environment, which results in an imbalance in the balanced relationship between a person and his environment, and the apprehension of the individual and society for fear of This posed a threat to their future, and the idea of sustainable development was subsequently developed. Sustainable development lies at the meeting point between the environment, the economy, and society. Therefore, most state governments work to make the world's population more aware, aware, and interested in the environment, so that they possess knowledge, skill, and commitment to work as individuals, or as groups, in order to find solutions to environmental problems and prevent new problems from arising. In the future. This study came to address the topic of sustainable development (the concept, and defining its dimensions. What are the most important challenges facing the means of achieving them on the ground, and finally concluded the most important results and solutions expected to reduce the phenomenon now and in the future .. The importance of this study lies in the fact that it allows diagnosing sustainable development and identifying the various challenges Algeria faces in this field.
The dimensions of sustainable development in Algeria and the idea of linking them to international trade
الملتقى الدولي الثامن حول: الاتجاهات الحديثة للتجارة الدولية وتحديات التنمية المستدامة نحو رؤى مستقبلية واعدة للدول النامية 02/ 03 ديسمبر 2019 - كلية العلوم الاقتصادية والتجارية وعلوم التسيير - جامعة الشهيد حمه لخضر - الوادي
Keywords: التنمية المستدامة -أبعاد –تحديات- خطط واستراتيجيات تنموية- التجارة الدولية; sustainable development- Dimensions-Challenges-Development plans and strategies- International Trade